Difunctional hydrogel as well as preparation method and application thereof
A bifunctional hydrogel encapsulating hydrophobic drugs and a thermal decomposition initiator addresses the limitations of current OSCC treatments by providing effective cancer cell elimination and bone regeneration through photothermal synergistic therapy and structural support.
Patent Information
- Application Number
- CN202411334410.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
Current treatments for oral squamous cell carcinoma (OSCC) face challenges in effectively eliminating residual tumor cells and repairing bone defects post-surgery, with existing therapies causing severe side effects and limited efficacy due to hypoxic tumor microenvironments and complex bone anatomy, while injectable hydrogels struggle with loading hydrophobic drugs and ensuring targeted delivery.
A bifunctional hydrogel composed of F127@ICG micelles, alpha-cyclodextrin-modified hyaluronic acid, and a thermal decomposition alkyl free radical initiator is developed, allowing for encapsulation of hydrophobic drugs and photothermal synergistic therapy to target cancer cells under hypoxic conditions, while also providing structural support for bone regeneration.
The hydrogel effectively kills cancer cells in hypoxic environments and promotes bone tissue regeneration by combining photothermal therapy with thermodynamic treatment, achieving targeted drug delivery and bone defect repair with minimal tissue damage.
Smart Images

Figure CN119185181A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomaterials, and in particular relates to a dual-functional hydrogel and a preparation method and application thereof. Background Art
[0002] Oral and maxillofacial tumors refer to tumors that occur in the oral cavity, salivary glands, maxillary and mandibular bones, face and neck, among which more than 90% of the pathological types are oral squamous cell carcinoma (OSCC). According to statistics, about 3.8 million people die from this disease and related diseases every year, and the incidence and mortality rates are increasing year by year. OSCC is highly heterogeneous, invasive and metastatic, and is usually treated with radical resection and radiotherapy and chemotherapy. However, due to the complex anatomy of the oral tissues and the close proximity of adjacent organs, radical resection is destructive to the host and often causes bone defects in the oral and maxillofacial regions, which may cause physiological dysfunctions such as chewing disorders, voice changes and dysphagia in patients, thereby reducing the quality of life and physical and mental health of patients. Bone defects caused by tumors usually have irregular shaped cavities. At present, synthetic bone substitute materials such as hydroxyapatite are often used for filling treatment in clinical practice, which often face many problems when used, such as complex operation, difficult shape matching and large trauma. In addition, for most patients, residual tumor cells may still exist in the local resection margin after surgical resection of the tumor, which requires adjuvant radiotherapy / chemotherapy. However, high-dose radiotherapy may induce radionecrosis of the jaw, and long-term chemotherapy may also induce tumor cell resistance, leading to tumor recurrence and metastasis and the ultimate death of the patient. Therefore, it is urgent to develop new treatment strategies that can avoid the serious toxic side effects of radiotherapy / chemotherapy and achieve the dual goals of ablation of residual tumor cells after OSCC tissue resection and repair and regeneration of bone defects caused by surgery, which is of great significance to improve the survival rate after OSCC surgery, reduce the mortality rate and improve the quality of life of patients.
[0003] At present, biomaterial-mediated tumor phototherapy, especially photothermal therapy (PTT) / photodynamic therapy (PDT) synergistic therapy, has shown great potential for clinical application. PTT is a non-invasive therapy that uses photothermal converters to convert light energy into thermal energy under the irradiation of external light sources such as near-infrared (NIR) light. However, the excessively high temperature (>50°C) of PTT will inevitably cause damage to the surrounding normal tissues, and considering the limited penetration of near-infrared light, PTT is only effective for superficial or small tumors. PDT activates photosensitizers through light to produce reactive oxygen species (ROS) to kill tumor cells, and can serve as an important supplement to PTT. However, most of the photosensitizers that have been commercialized and are under research generate singlet oxygen (ROS) through energy transfer. 1 O2) is a type II photosensitizer. This process is highly dependent on oxygen concentration. However, due to the aggressive proliferation of cancer cells and insufficient blood supply to the tumor, a severe hypoxic tumor microenvironment appears in solid tumors, which has a significant negative impact on oxygen-dependent PDT. Therefore, the development of a non-oxygen-dependent photothermal synergistic therapy model is the key to further improving the effect of cancer phototherapy. Thermodynamic therapy (TDT) is a new type of non-oxygen-dependent cancer treatment mediated by highly toxic alkyl free radicals. It mainly uses highly toxic alkyl free radicals generated by thermal decomposition free radical initiators (such as azo compounds) after heating to induce cell apoptosis and necrosis. By combining TDT with PTT, not only can a relatively mild temperature be used to reduce thermal damage to surrounding normal tissues, but it can also overcome the adverse effects of the tumor hypoxic microenvironment on PDT, and carry out more effective cancer synergistic therapy.
[0004] In addition, bone defects caused by OSCC surgery also require effective repair strategies. In recent years, a variety of materials have been developed to accelerate the repair of bone defects, including organic materials, inorganic materials, and composite materials. Injectable hydrogels with organic macromolecules as the skeleton are organic materials with a three-dimensional network structure similar to the extracellular matrix. These hydrogels can provide a scaffold structure to promote the attachment and proliferation of bone cells, and provide a carrier for growth factors to promote osteoblast differentiation and new bone formation. In addition, injectable hydrogels can adapt to irregular-shaped bone defects, adhere tightly to the implantation site, are easy to operate, and have the characteristics of non-invasiveness and minimally invasiveness. They have unique advantages in the treatment of mandibular defects. Injectable hydrogel materials can be divided into natural and synthetic sources. Natural polymers such as chitosan, alginate, hyaluronic acid (HA), collagen, gelatin, etc. have the advantages of being biodegradable and carrying integrin binding sites, but they are immunogenic. Artificial synthetic polymers, such as polyethylene glycol (PEG), polyacrylamide, polyvinyl alcohol and polymethyl methacrylate, have advantages such as strong mechanical properties, customizability and low immunogenicity, but lack inherent biological functions and must undergo important post-processing to induce the desired response in vivo. Combining the two to prepare injectable hydrogels can improve their mechanical strength and stability, achieve precise control of porosity, grid structure and release behavior, and at the same time give hydrogels good cell adhesion and proliferation, provide better filling effects, and promote bone tissue regeneration and healing.
[0005] Typically, before administration, drugs and cells are loaded into injectable hydrogels by mixing aqueous solutions of hydrogel components, a relatively simple process. As a local drug delivery system, hydrogels can gradually swell or degrade at the injection site, thereby providing sustained, targeted release of bioactive agents. However, for some hydrophobic drugs, they have inherent incompatibility with hydrophilic gel networks, so how to effectively load hydrophobic drugs into hydrogels remains a challenge. In addition, for some naked drugs that are not wrapped and protected and released directly from the delivery system, they have low stability in vivo, especially for some hydrophobic drugs and nucleic acid drugs, which often find it difficult to penetrate the cell membrane to reach the intracellular target, resulting in extremely low bioavailability. Therefore, making hydrogel drug delivery have dual goals, including how to load hydrophobic drugs into hydrogels and deliver drugs to target cells, is a technical problem that urgently needs to be solved. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a dual-functional hydrogel and a preparation method and application thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A bifunctional hydrogel comprises F127@I CG micelles, alpha-cyclodextrin-modified hyaluronic acid, a thermal decomposition type alkyl free radical initiator and water; preferably, the F127@I CG micelles are composite micelles formed by self-assembly of P l uronic F127 and a photothermal conversion agent ICG.
[0009] The thermal decomposition type alkyl free radical initiator is AIPH; the mass concentration of the initiator is 0.01-5%, preferably 1.25%.
[0010] The mass concentration of α-cyclodextrin modified hyaluronic acid in the dual-functional hydrogel system is ≥7.5%, preferably 10%; the grafting rate of α-cyclodextrin modified hyaluronic acid HA-CD is between 10% and 45%, preferably 11.6%.
[0011] The final concentration of the F127@I CG micelles is 5-15%, preferably 13.4%; the I CG concentration is 0.01-1%, preferably 0.1%;
[0012] Preferably, the hydrated particle size of the F127@I CG micelle is 50-500 nm, and the polydispersity index is 0.15-0.35; preferably, the hydrated particle size of the F127@I CG micelle is 269.7 nm, and the polydispersity index is 0.2563.
[0013] The α-cyclodextrin modified hyaluronic acid HA-CD is prepared by the following method: hyaluronic acid and amino-modified α-cyclodextrin are reacted under the action of a condensing agent and a catalyst; the relative molecular mass of the hyaluronic acid is in the range of 30 kDa to 600 kDa, preferably 30 kDa;
[0014] Preferably, the condensing agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride; the catalyst is N-hydroxysuccinimide sulfonic acid sodium salt;
[0015] Preferably, the mass ratio of the hyaluronic acid to the amino-modified α-cyclodextrin is 1:(0.1-1); preferably 1:0.5;
[0016] Preferably, the method comprises the following steps: 1) dissolving hyaluronic acid in morpholineethanesulfonic acid buffer, adding a condensing agent and a catalyst, and stirring at room temperature for 0.5h-4h; 2) adjusting the pH of the reaction system to 7.2 with a phosphate buffer, and then adding amino-modified α-cyclodextrin, stirring at room temperature for 12-24h; 3) dialyzing in deionized water for 3-5 days, and freeze-drying to obtain α-cyclodextrin-modified hyaluronic acid. Preferably, the concentration of the morpholineethanesulfonic acid buffer is 0.1M, and the pH is 5; the concentration of the phosphate buffer is 0.1M, and the pH is 7.4.
[0017] F127@I CG micelles are prepared by the following method: 1) adding a chloroform solution of the photothermal conversion agent I CG to a Pluronic F127 aqueous solution, immediately ultrasonicating for 3-5 min, and stirring at room temperature for 12-24 h; preferably, the ultrasonic treatment conditions are: 125w, 5s / 5s on / off cycle, 3 minutes; 2) after the chloroform is completely evaporated, post-treatment is performed using an ultrafiltration tube to obtain F127@I CG micelles; preferably, post-treatment is performed using an ultrafiltration tube with MWCO=3500Da and centrifuged at 6000-10000rpm for 30-60min to obtain micelles F127@I CG.
[0018] The present invention also includes a method for preparing the bifunctional hydrogel, comprising the following steps: 1) dissolving α-cyclodextrin-modified hyaluronic acid HA-CD in deionized water at room temperature, stirring thoroughly, and standing; 2) adding a thermal decomposition type alkyl free radical initiator to the HA-CD solution to fully dissolve it; 3) adding F127@I CG micelles to the above solution, stirring thoroughly, mixing evenly, standing at room temperature for 30-120 minutes, and sterilizing with ultraviolet light to obtain PFHA@I CG / AIPH.
[0019] The present invention also includes an application of the dual-functional hydrogel, which is used to prepare an injectable hydrogel with thermodynamic treatment function and oral and mandibular defect repair function; the concentration of the hydrogel is ≤10 mg / mL, preferably 4.7 mg / mL.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] Cyclodextrin (CD)-based host-guest supramolecular hydrogels have excellent biocompatibility, shear thinning and stimulus responsiveness, and have developed into a series of hydrogels suitable for biomedical applications. From the perspective of composition and structural characteristics, CD host-guest supramolecular hydrogels can be divided into supramolecular hydrogels derived from poly(pseudo)rotaxanes and supramolecular hydrogels with host-guest interactions between CD and small guest molecules. Among them, polyquasi-polyrotaxane supramolecular hydrogels prepared by inclusion complexation of α-CD and PEG show great application prospects in the field of drug controlled release due to mild preparation conditions, good biocompatibility and shear thinning. Pluronic F127 is a block polymer containing two PEG chains, which are connected by a hydrophobic polypropylene alcohol part and show unique amphiphilicity. It is widely used in the fields of drug delivery and biomaterials, especially for hydrophobic drugs, it can improve their solubility, in vivo circulation half-life and adverse reactions, and can also enhance the permeability and retention effect of drugs in tumor tissues, realizing multiple drug loading and controlled release of drugs.
[0022] The present invention firstly encapsulates the hydrophobic photothermal conversion agent indocyanine green (ICG) into Pluronic F127 to prepare F127@ICG micelles, and further dissolves the thermal decomposition type alkyl free radical initiator 2,2'-azobis[2-(2-imidazolin-2-yl)propane]-dihydrochloride (AIPH) into α-cyclodextrin-modified hyaluronic acid (HA-CD), and then mixes the obtained mixed solution with the F127@ICG micelle solution at room temperature to obtain the poly-quasi-polyrotaxane supramolecular hydrogel PFHA@ICG / AIPH co-loaded with ICG and AIPH. Under near-infrared light irradiation, the photothermal effect of ICG is used to induce AIPH to be rapidly released and decomposed at the tumor site, generating free radicals, thereby effectively killing cancer cells in the hypoxic environment of OSCC, and having a better anti-tumor therapeutic effect. In addition, the hydrogel can also be filled in the bone defect area to provide structural support for the proliferation and differentiation of bone marrow mesenchymal stem cells after tumor removal, guide the formation of new bone matrix, thereby inducing the regeneration of bone tissue and achieving effective repair of bone tissue defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1This is the hydrogen nuclear magnetic resonance spectrum (300 MHz, D2O) of the α-cyclodextrin-modified hyaluronic acid HA-CD synthesized in Example 1 of the present invention;
[0024] Figure 2 is a particle size distribution diagram (A) and a TEM image (B) of the F127@I CG micelles prepared in Example 2 of the present invention;
[0025] Figure 3 The images of the gel after mixing different concentrations of HA-CD and F127@I CG micelles in Example 3 of the present invention (A); and the G' and G" of the hydrogel prepared using HA-CD with a concentration of 20wt% as a function of ω (B) and SEM image (C);
[0026] Figure 4 The pictures of the gelation time of the hydrogel in Example 4 of the present invention (A), the pictures of the hydrogel extruded through a 26# needle for injection (B), and the G' and G" of the hydrogel prepared with HA-CD having a final concentration of 10 wt% as a function of stress (C);
[0027] Figure 5 is the temperature rise curve of the hydrogel in Example 5 of the present invention at different time points under the irradiation of lasers (808 nm) with different power densities;
[0028] Figure 6 The CCK8 method is used in Example 6 of the present invention to detect the cytotoxicity of the hydrogel to Cal-27 cells (A) and MC3T3-E1 cells (B);
[0029] Figure 7 The CCK8 method was used in Example 7 of the present invention to measure the Ca l-27 cells and 4.7 μg mL -1 The hydrogels were incubated and then irradiated with laser (0.75 W / cm 2 , 5 min) Cell survival rate after continued culture for 12 h;
[0030] Figure 8 This is the experimental result of the hydrogel repairing the critical bone defect model of the rabbit jaw in Example 8 of the present invention. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.
[0032] Example 1: HA (1000 mg, M w=30kDa) was dissolved in 150mL morpholineethanesulfonic acid buffer (0.1M, pH=5), N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (1524.0mg, 7.9mmol) and N-hydroxysuccinimide sulfonic acid sodium salt (1000mg, 4.6mmol) were added, stirred at room temperature for 1h, the pH of the above reaction system was adjusted to 7.2 with phosphate buffer (0.1M, pH=7.4), amino-modified α-cyclodextrin (500mg, 0.51mmol) was added, and stirred at room temperature for 12h. It was dialyzed in deionized water (MWCO=3500Da) for 5 days and freeze-dried to obtain α-cyclodextrin-modified hyaluronic acid HA-CD.
[0033] The structure of the product was analyzed by Varian 400MHz NMR spectrometer. Figure 1 As shown, the signal at 4.73ppm is attributed to the solvent D2O, the two double peaks of δ4.41 and 4.32 are the two proton peaks of HA hemiacetal, the peak of δ1.89 is the methyl proton peak of HA, the peak of δ4.93 is attributed to the signal peak of the proton hydrogen at the C1 position of cyclodextrin, and the chemical shifts of the remaining proton peaks of α-CD and HA are in the range of 4.01-3.02ppm, which indicates that HA-CD has been successfully synthesized. The ratio of the integrated area of HA at δ4.53-4.24 to the integrated area of α-CD at δ4.93 is used to infer that the grafting rate of α-CD on HA is about 11.6%.
[0034] Example 2: ICG chloroform solution (1 mg / mL, 1 mL) was added to Polyuronic F127 aqueous solution (2%, 5 mL), and then ultrasonicated (35 W, on / off cycle, 5 s / 5 s) for 3 min, stirred overnight at room temperature, and purified and collected micelles by centrifugation (6000 rpm, 60 min) using an ultrafiltration tube (MWCO = 3500 Da). After washing with deionized water and resuspending, the particle size of the micelles was detected by Malvern Zetas i zer Nano-ZS dynamic light scattering (DLS).
[0035] Transmission electron microscopy (TEM) was used to observe the morphology of micelles. Figure 2 As shown in A, the hydrated particle size of F127@I CG is 269.7nm, and the polydispersity index is 0.2563, showing a unimodal distribution, indicating good dispersion. Transmission electron microscopy ( Figure 2 B) analysis showed that the micelles were uniform and clear spherical with a size of 180 ± 5 nm, which was slightly smaller than the particle size detected by DLS, which may be due to the shrinkage of the particles in the dry state.
[0036] Example 3: The HA-CD synthesized in step 1 was dissolved in deionized water at different concentrations, and an equal amount of AIPH was dissolved therein, and then equal volumes of F127@I CG micelle solution (concentration 26.8%) were added respectively, and the mixture was thoroughly stirred to obtain final concentrations of HA-CD in the mixed solution of 2.5wt%, 5wt%, 7.5wt%, and 10wt%, respectively, and the final concentrations of F127@I CG micelle solution were all 13.4% (the final concentration of F127 was 13.3%, and the final concentration of I CG was 0.1%), and the final concentration of AIPH was 1.25%. The gelation effect was observed at room temperature.
[0037] The results show that ( Figure 3 A) When the final concentration of HA-CD was 2.5wt% and 5wt%, the mixed solution was a flowing liquid and failed to gel. When the final concentration of HA-CD was 7.5wt% and 10wt%, the mixed solution gelled after being left overnight, indicating that the minimum gelation concentration of HA-CD is above 7.5wt%.
[0038] Hydrogels with a final HA-CD concentration of 10 wt% were selected for rheological testing on a rheometer. The storage modulus (G') and loss modulus (G") of the hydrogels were measured by frequency scanning in the oscillation mode with an angular frequency of 0.1-100 rad / s. The test was carried out at 25 °C.
[0039] like Figure 3 As shown in B, within the test frequency range, in the low frequency band (0.1-1rad / s), G' and G" gradually decrease, the molecular chains quickly rearrange, and the characteristics of the fluid are revealed. In the medium frequency band (1-62rad / s), G' and G" tend to be stable, showing obvious solid characteristics. In the high frequency band (62-100rad / s), G' and G" gradually decrease again, and the molecular weight cannot keep up with the change of the external stress, showing more fluid characteristics. After rapid freezing in liquid nitrogen and storing at -80℃ overnight, freeze-drying (condensation temperature <-54℃, vacuum degree <20Pa), the sample is sprayed with gold under vacuum conditions, and the sprayed sample is placed in a scanning electron microscope (SEM). It can be observed that the hydrogel has a three-dimensional cross-network structure with a uniform and high-density pore distribution, which is conducive to the encapsulation and controlled release of AIPH and I CG.
[0040] Example 4: After the F127@I CG micelles obtained in Example 2 were mixed with the HA-CD solution, the sample bottle was tilted 45° every 1 minute until the liquid in the sample bottle stopped flowing, and the gelation time of the hydrogel PFHA@I CG / AIPH was determined accordingly. The gelation time of the hydrogel with a final HA-CD concentration of 7.5wt% was 8h (data not shown). After mixing with the F127@I CG micelles, the mixed solution with a final HA-CD concentration of 10wt% could gel in 30min ( Figure 4 A), indicating that as the concentration of HA-CD increases, the gelation time shortens. At this time, the weight ratios of F127@I CG, HA-CD and AIPH in the injectable hydrogel PFHA@I CG / AIPH are 13.4%, 10.00% and 1.25% respectively. In addition, before the hydrogel is gelled, the blended solution is loaded into a syringe and squeezed out through a 26# needle. Figure 4 B shows that the hydrogel can be easily extruded, indicating that it is injectable.
[0041] The G' and G" ( Figure 4 C) It was found that under small strain conditions, G'>G", indicating that the solid-like elastic behavior of the hydrogel is dominant and can maintain its own integrity. As the strain increases, both G' and G" decrease, and the mechanical properties of the hydrogel weaken. This may be due to the destruction of the gel network structure caused by the applied strain, which eventually intersected at the cross strain (6%). After that, G'<G", indicating that there is an obvious viscous response. The hydrogel is easier to flow and deform under large strain conditions, showing injectable properties.
[0042] Example 5: Characterization of the photothermal effect of hydrogel at room temperature 26°C and humidity 65%. 0.5 mL of hydrogel (concentration 2.66 mg / mL, where I CG concentration is 20 μg mL -1 , AIPH concentration was 250 μg mL -1 ) were placed in a 48-well plate and an 808 nm laser was used at different power densities (0.5-1.5 W / cm 2 ) for 10 minutes, monitor the temperature rise every minute by an electronic thermometer with a thermocouple probe, and make a temperature rise curve based on the temperature displayed by the instrument.
[0043] The results are as follows Figure 5 As shown, as the power density increases from 0.5W / cm 2 Increase to 1.5W / cm 2 , the temperature rises from 43.3℃ to 55.6℃. Among them, when the power density is 0.75W / cm 2The temperature reached 42.6°C after 5 minutes of irradiation and was maintained between 42.6°C and 43.8°C for the next 5-10 minutes, which meets the temperature requirements of mild photothermal therapy. Therefore, 0.75W / cm 2 was chosen as the power density for subsequent cell experiments.
[0044] Example 6: In order to better evaluate the biosafety of the hydrogel, human tongue squamous cell carcinoma cell Cal-27 and mouse embryonic osteoblast precursor cell MC3T3-E1 were inoculated in 96-well plates, with an inoculation density of 5000 cells / well, cultured overnight in a cell culture incubator at 37°C and 5% CO2, and different concentrations of hydrogel were added. After incubation for 24 hours, the survival rate of the hydrogel was evaluated by CCK-8 detection. For Cal-27 cells, even at a concentration of up to 10 mg / mL, the cell survival rate can still reach more than 90%, indicating that the hydrogel is not toxic to Cal-27 cells. For MC3T3-E1 cells, when the concentration reaches 8 mg / mL, the cell survival rate is above 70%, and there is no obvious cytotoxicity at this time, but when the concentration is ≥10 mg / mL, the cell survival rate is less than 70%, and potential cytotoxicity occurs, so the subsequent implementation is selected to be carried out within the range of less than 10 mg / mL.
[0045] Example 7: In order to evaluate the thermodynamic therapeutic effect of hydrogel on tumors, in vitro, Cal-27 cells were seeded in a 48-well plate at a seeding density of 50,000 cells / well and cultured overnight in a cell culture incubator at 37°C and 5% CO2. 4.7 mg / mL of hydrogel (with an ICG concentration of 20 μg / mL and an AIPH concentration of 250 μg / mL) was co-incubated with the cells for 2 h, and then the cells were irradiated with an 808 nm laser (0.75 W / cm 2 , 5min), and the cells without laser irradiation were used as control. After irradiation, the cells were cultured for 12h, and the CCK-8 method was used to detect the effect of in vitro thermodynamic therapy.
[0046] turn out( Figure 7), in the absence of laser irradiation, the survival rate of free ICG was 90.3%, while the survival rate of the mixture of free ICG and free AIPH was 72.8%, which indicates that AIPH will produce a certain amount of free radicals when incubated at 37°C, causing a certain degree of damage to the cells. In contrast, the cell survival rates of PFHA@ICG and PFHA@ICG / AIPH using hydrogel as carriers exceeded 100%, indicating that the hydrogel carrier can effectively reduce the toxicity of free drugs. After applying laser to the cells, the survival rate of the group without drug addition was 101.5%, indicating that the laser itself had no significant effect on the activity of the cells. In the drug-added groups, the survival rates decreased significantly, among which the survival rate of PFHA@I CG / AIPH decreased most significantly, which was lower than that of the PFHA@ICG group. This indicates that the polyquasi-polyrotaxane supramolecular hydrogel PFHA@I CG / AIPH co-loaded with I CG and AIPH can utilize the photothermal effect of I CG to induce the rapid release and decomposition of AIPH at the tumor site under near-infrared light irradiation, generate free radicals, and thus effectively kill cancer cells, with better tumor killing effect.
[0047] Example 8: In order to evaluate the bone repair effect of injectable hydrogel, rabbits were given general anesthesia and the mandibular area was exposed. A circular bone defect with a diameter of 5 mm and a depth of 2 mm was created in the body of the rabbit's mandible using a 5 mm diameter drill. The hydrogel was injected into the bone defect area and the incision was sutured. The healing of the bone defect area was checked at the 8th and 12th weeks after surgery, and X-ray scans were taken for evaluation. The results in the figure show that after 12 weeks of hydrogel implantation, about 40% of the bone tissue can be repaired. Compared with the blank group, the injection of hydrogel has a certain degree of promoting effect on the repair of bone tissue.
[0048] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A bifunctional hydrogel, characterized in that: It comprises F127@ICG micelles, alpha-cyclodextrin modified hyaluronic acid, a thermal decomposition type alkyl free radical initiator and water; preferably, the F127@ICG micelles are composite micelles formed by self-assembly of Pluronic F127 and photothermal conversion agent ICG.
2. The bifunctional hydrogel according to claim 1, characterized in that: The thermal decomposition type alkyl free radical initiator is AIPH; the mass concentration of the initiator is 0.01-5%, preferably 1.25%.
3. The bifunctional hydrogel according to claim 1, characterized in that: The mass concentration of α-cyclodextrin modified hyaluronic acid in the dual-functional hydrogel system is ≥7.5%, preferably 10%; the grafting rate of α-cyclodextrin modified hyaluronic acid HA-CD is between 10% and 45%, preferably 11.6%.
4. The bifunctional hydrogel according to claim 1, characterized in that: The final concentration of the F127@ICG micelles is 5-15%, preferably 13.4%; the ICG concentration is 0.01-1%, preferably 0.1%; Preferably, the hydrated particle size of the F127@ICG micelle is 50-500 nm, and the polydispersity index is 0.15-0.35; preferably, the hydrated particle size of the F127@ICG micelle is 269.7 nm, and the polydispersity index is 0.2563.
5. The bifunctional hydrogel according to claim 1, characterized in that: The α-cyclodextrin modified hyaluronic acid HA-CD is prepared by the following method: hyaluronic acid and amino-modified α-cyclodextrin are reacted under the action of a condensing agent and a catalyst; the relative molecular mass of the hyaluronic acid is in the range of 30 kDa to 600 kDa, preferably 30 kDa; Preferably, the condensing agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride; the catalyst is N-hydroxysuccinimide sulfonic acid sodium salt; Preferably, the mass ratio of the hyaluronic acid to the amino-modified α-cyclodextrin is 1:(0.1-1); preferably 1:0.5; Preferably, the method comprises the following steps: 1) dissolving hyaluronic acid in morpholineethanesulfonic acid buffer, adding a condensing agent and a catalyst, and stirring at room temperature for 0.5h-4h; 2) adjusting the pH of the reaction system to 7.2 with a phosphate buffer, and then adding amino-modified α-cyclodextrin, stirring at room temperature for 12-24h; 3) dialyzing in deionized water for 3-5 days, and freeze-drying to obtain α-cyclodextrin-modified hyaluronic acid. Preferably, the concentration of the morpholineethanesulfonic acid buffer is 0.1M, and the pH is 5; the concentration of the phosphate buffer is 0.1M, and the pH is 7.
4.
6. The bifunctional hydrogel according to claim 1, characterized in that: F127@ICG micelles were prepared by the following method: 1) adding a chloroform solution of the photothermal conversion agent ICG to an aqueous solution of Pluronic F127, immediately ultrasonicating for 3-5 min, and stirring at room temperature for 12-24 h; preferably, the ultrasonic treatment conditions are: 125w, 5s / 5s on / off cycle, 3 minutes; 2) after the chloroform is completely evaporated, post-treatment is performed using an ultrafiltration tube to obtain F127@ICG micelles; preferably, post-treatment is performed using an ultrafiltration tube with MWCO=3500Da and centrifuged at 6000-10000rpm for 30-60min to obtain micelles F127@ICG.
7. A method for preparing the bifunctional hydrogel according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: 1) dissolving α-cyclodextrin-modified hyaluronic acid HA-CD in deionized water at room temperature, stirring the solution thoroughly and allowing the solution to stand; 2) adding a thermal decomposition type alkyl free radical initiator to the HA-CD solution to allow the solution to be fully dissolved; 3) adding F127@ICG micelles to the above solution, stirring the solution thoroughly, mixing the mixture evenly, allowing the solution to stand at room temperature for 30-120 minutes, and sterilizing the solution with an ultraviolet lamp to obtain PFHA@ICG / AIPH.
8. An application of the bifunctional hydrogel according to any one of claims 1 to 6, characterized in that: It is used to prepare injectable hydrogels with thermodynamic treatment function and oral and mandibular defect repair function; the concentration of the hydrogel is ≤10 mg / mL, preferably 4.7 mg / mL.